Cinchona Alkaloid Catalyzed Dynamic Kinetic Resolution of Biaryl Aldehydes via Asymmetric Decarboxylative Transamination - Guo, Donghui; Wang, Jian (Synthesis, 2022)
An unprecedented Cinchona alkaloid catalyzed atropoenantioselective transamination of biaryl aldehydes with 2,2-diphenylglycine via a cascade decarboxylation and dynamic kinetic resolution strategy is described. This protocol features broad substrate scope and good functional group tolerance and allows the rapid assembly of axially chiral biaryls in high yields with acceptable to good enantioselectivities. In addition, such structural motifs may have potential applications in enantioselective catalysis as chiral ligands or catalysts.
Keywords: dynamic kinetic resolution; transamination; asymmetric organocatalysis; axially chiral biaryls; cinchona alkaloid